A5_7 Neutron activation of the Unity Node of the ISS - Lipscombe, Giles; Penney, Jordan; Allison, Hayley Jane; Leyser, Roger (Physics Special Topics, 2014)
The paper describes the calculation of the annual radiation dose of an astronaut on the ISS from gamma rays created by solar neutron activation of the aluminium structure of the Unity Node. It is calculated that the annual dose is 2.32 x 10-5 mSv, and the solar neutron flux required to reach the maximum legal annual dose is 828 neutrons cm-3 s-1. The results show that the annual neutron activation gamma ray dose is very small compared to the legal limit (some six orders of magnitude smaller).